2011
DOI: 10.1007/s11144-011-0311-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure on the mechanisms of the CO2/H2 reaction on a CO-precipitated CuO/ZnO/Al2O3 catalyst

Abstract: The influence of working pressure on the mechanisms of the CO 2 /H 2 reaction on a co-precipitated CuO/ZnO/Al 2 O 3 catalyst have been studied at 230°C and in the pressure range of 1-75 bar. In the CO 2 hydrogenation using CuO/ZnO/ Al 2 O 3 , the products were found to be CO, methanol and water almost exclusively. Only a trace of methane formation was observed. Methanol and carbon monoxide are competitively formed. The former is produced directly from CO 2 whatever the pressure whereas carbon monoxide stems ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…As pressure increases, methanol production is enhanced by up to about five times, and at the same time, the selectivity to methanol as compared to CO is also promoted. Overall, higher pressure greatly benefits CO 2 hydrogenation to methanol, which is consistent to other researches . However, it should be noted that although increase of the pressure (up to 40 bar) can enhance the conversion as well as the selectivity of the reaction, the extent of the improvement was limited .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…As pressure increases, methanol production is enhanced by up to about five times, and at the same time, the selectivity to methanol as compared to CO is also promoted. Overall, higher pressure greatly benefits CO 2 hydrogenation to methanol, which is consistent to other researches . However, it should be noted that although increase of the pressure (up to 40 bar) can enhance the conversion as well as the selectivity of the reaction, the extent of the improvement was limited .…”
Section: Resultssupporting
confidence: 86%
“…Overall, higher pressure greatly benefits CO 2 hydrogenation to methanol, which is consistent to other researches . However, it should be noted that although increase of the pressure (up to 40 bar) can enhance the conversion as well as the selectivity of the reaction, the extent of the improvement was limited . Thus, design and implementation of novel nanoengineered catalysts, such as the nanorod array catalysts developed in this study, are important for revolutionary improvement of the process.…”
Section: Resultssupporting
confidence: 85%
“…As shown in Table S1, a comparative study of the activity data of this novel catalyst with the reported literature revealed that CHT-F0.9 exhibited much better catalytic performance as compared to that over the conventional Cu/ZnO/Al 2 O 3 catalyst prepared by coprecipitation method under similar reaction conditions [47,48].…”
Section: Catalytic Performancementioning
confidence: 70%
“…It is experimentally known that at low pressures, methanol is formed via the formate route, but at higher pressure the RWGS route also becomes accessible. 45 We see that except at 20 bar, the selectivity of the Zn 3 O 3 /Cu catalyst is better than that of Mg 3 O 3 /Cu.…”
Section: Kmc Simulationsmentioning
confidence: 73%
“…It has been reported in the literature that higher amounts of chemisorbed hydrogen are also due to the formation of subsurface hydrogen. 45 Surface area is the largest for Cu/Mg, followed by Zn, Cr, and Fe. The relatively low surface area of Cu/Cr and Cu/Fe catalysts (in comparison to Cu/Zn and Cu/Mg) could be caused by blocking of the alumina pores with the crystallites of chromium and iron oxides.…”
Section: Kmc Simulationsmentioning
confidence: 96%